Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
In July 2017, the CHSSN submitted the present report to the Quebec Ministry of Health and Social Services inviting it to undertake consultations with key public institutions and community representatives with respect to the recommendations. The objective was to ensure that a proposal to Health Canada reflected the shared commitment of Quebec and its English-speaking communities to work in partnership to improve access to health and social services in English. In its reply to the CHSSN in October 2017 (Appendix), the Ministry supported the recommendations in accordance with comments reflecting the results of its consultations with the public institutions. To support Health Canada in its mandate to prepare a new Contribution Program, the sponsoring organizations of the twenty recognized community health and social services networks along with the CHSSN are submitting the present report and recommendations reflecting the continuity of results of the last federal contribution and emergence of new priorities for the period ahead.
Keywords: Official Language Minority Community (OLMC)

English-speaking Communities of the Gaspésie – Îles-de-la-Madeleine: A Regional Profile - Richardson, Mary; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)

Promoting the Health and Well-being of English Speaking Seniors in Quebec : A Community Model - Kueber, Russell; Pocock, Joanne; Hobbs-Robert, Jennifer; Hale, Jeffery (Community Health and Social Services Network (CHSSN), 2019)
This document describes a community model for improving the health and well-being of a linguistic minority senior population in Quebec. English-speaking seniors have unique challenges due to language barriers, socioeconomic inequalities as well as the lack of awareness of their needs and lack of representation associated with the minority status of their community. Many community organizations have recognized the critical level of vulnerability of this population and have designed and implemented successful strategies to address these challenges while remaining aligned with the Quebec government's comprehensive strategies and approaches on healthy aging such as Vieillir et vivre ensemble and Municipalite amie des aines. The main purpose of the document is to help inform and guide English-speaking communities and their community and public partners in their ongoing collaborative efforts to effectively adapt programs and services to improve the lives of English-speaking seniors in their communities.